2018
DOI: 10.1177/0893318918755506
|View full text |Cite
|
Sign up to set email alerts
|

Managing Illegitimate Task Requests Through Explanation and Acknowledgment: A Discursive Leadership Approach

Abstract: This study explored how discursive framing can mitigate an illegitimate task request-a request from a supervisor that extends beyond the appropriate parameters of the role. Using hypothetical vignettes in an experimental design, we examined how including an acknowledgment and/or explanation when making an illegitimate task request mitigated perceptions of illegitimacy and anger. Results indicate that acknowledgments mitigated perceptions of illegitimacy whereas explanations mitigated anger. Furthermore, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 57 publications
1
11
0
1
Order By: Relevance
“…If assigning illegitimate tasks is unavoidable (after all, organizational necessities may demand it), supervisors should show respect by acknowledging that a task may be considered illegitimate by the employee and by explaining why they assign the task nevertheless ("I know this is not your job, but…"). Corresponding to interactional fairness (Bies, 2015;Tyler, 2012), such explanations may "legitimize" the task assignment and thus avoid, or at least alleviate, its potential negative impact as recently shown in a study by Minei et al (2018). Second, supervisors (and others in the organization), should realize the importance of appreciating others and their achievements.…”
Section: Practical Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…If assigning illegitimate tasks is unavoidable (after all, organizational necessities may demand it), supervisors should show respect by acknowledging that a task may be considered illegitimate by the employee and by explaining why they assign the task nevertheless ("I know this is not your job, but…"). Corresponding to interactional fairness (Bies, 2015;Tyler, 2012), such explanations may "legitimize" the task assignment and thus avoid, or at least alleviate, its potential negative impact as recently shown in a study by Minei et al (2018). Second, supervisors (and others in the organization), should realize the importance of appreciating others and their achievements.…”
Section: Practical Implicationsmentioning
confidence: 96%
“…Di Fabio and Peiro (2018) have applied this concept to Human Capital Sustainable Leadership. By avoiding illegitimate tasks or, if that is not possible, offering acknowledgment and explanations (Minei et al, 2018), and thus preventing, or mitigating, offenses to the self, and by signaling appreciation, and thus acknowledging employees and their contributions, leaders as well as other organizational members can contribute to decent work. Furthermore, avoiding threats to, and offering affirmation of, the self implies respecting people's dignity (Semmer et al, 2007), which relates to justice (Miller, 2001) and to organizational ethics (Sekera et al, 2014;Meier et al, 2013).…”
Section: Theoretical Implications and Further Researchmentioning
confidence: 99%
“…Third, while we have explored only the lived experiences of leaders, Collinson (2005) and Cunliffe and Eriksen (2011) remind us that leaders and followers are co-constituted and that the discursive acts of colleagues, leaders, and followers must be incorporated to provide a richer context. In the future, interactions between leaders and followers could be analyzed (Minei et al, 2018) for their construction of knowing-not knowing. Fourth, another limitation of our study is that we have not investigated distinctions between leaders and managers.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that leaders use discursive tactics to mitigate perceptions of violating expectations of appropriate leadership behavior. For instance, Minei et al (2018) found that leaders used discursive tactics of “acknowledgment” and “explanation” when making an illegitimate task request to their followers in order to reduce the perceived illegitimacy of the request. Liu’s (2010) discursive analysis of leaders’ media texts revealed a typology of tactics used by leaders and others as a way of recovering from mistakes.…”
Section: Discourses Surrounding Leadership and Knowledge/knowingmentioning
confidence: 99%
“…Rather, tasks become illegitimate in a specific context. Previous research has shown that supervisors' framing (e.g., acknowledgment) may mitigate employees' perceptions of illegitimacy [43]. Such framing effects may also occur in the context of abusive supervision.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%